THE RISE OF CHINA AND ITS IMPLICATION ON INDONESIA-UNITED STATES TRADE - Putriani, Diyah; Azzani, Meikha (Journal of Indonesian Economy and Business, 2011)
The purpose of this study is to analyze the impact of Chinese renminbi exchange rateÂ againts the United States (US) dollar, on the bilateral export of Indonesia to the US.Johansen cointegration test and Ordinary Least Square (OLS) regression are employed toÂ examine one impact. This research is limited only in the long-run aspect. The Johansentest shows that there are long-run relationships amongs variables involved such as GDP,Â Real Exchange Rate (RER), RER Volatility, and dummy variables. Empirical test resultshows that there are positive significant impacts of the Chinese renminbi on theÂ Indonesiaâs exports to the US, implying that the relationship between Chinese exports andIndonesia export are complementary in the US market.Keywords: Indonesia, China, the United States, renminbi, cointegration, OLSÂ